2009
DOI: 10.1254/jphs.08283fp
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Renal Ischemia–Reperfusion Injury by Inhibition of IL-6 Production in the Poloxamer 407–Induced Mouse Model of Hyperlipidemia

Abstract: Abstract. It is largely unknown whether hyperlipidemia is involved in the pathobiology of renal ischemia-reperfusion (I/R) injury that is an important cause of acute kidney injury. Here we studied the effect of experimental dyslipidemia on renal I/R injury. Renal I/ R injury was less severe in hyperlipidemic mice treated with poloxamer 407 than in the control mice. Cytokine analyses revealed decreased levels of renal and serum IL-6 in the hyperlipidemic mice after renal I/ R. Protection from renal I /R injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Although P-407 is also a non-ionic surface active agent, like TritonWR 1339, but the physiological toxicity of P-407 is low and the plasma triglyceride level of mice can be maintained stably at 5000 mg/dl after the prolonged stimulation with P-40714. Compared with genetically modified animal models, this novel HTG model has the advantages of simple operation, low cost and plasma lipid matching with HTG-AP patients, consequently imitating the pathophysiological process of such patients well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although P-407 is also a non-ionic surface active agent, like TritonWR 1339, but the physiological toxicity of P-407 is low and the plasma triglyceride level of mice can be maintained stably at 5000 mg/dl after the prolonged stimulation with P-40714. Compared with genetically modified animal models, this novel HTG model has the advantages of simple operation, low cost and plasma lipid matching with HTG-AP patients, consequently imitating the pathophysiological process of such patients well.…”
Section: Discussionmentioning
confidence: 99%
“…Poloxamer 407 (P-407) is a hydrophilic triblock copolymer comprised of polyoxyethylene and polyoxypropylene units and has been reported to induce HTG with little side effects14. P-407 can increase the serum triglyceride concentrations by directly inhibiting the activity of both LPL and hepatic lipase, which were combined with the capillary wall1516.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sharyo et al (2009) [42], after anesthesia, an abdominal incision was made and the renal pedicles were dissected bilaterally. A vascular clamp (Biotechno, Germany) was placed on each renal pedicle for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the histamine antagonist ketotifen could improve the survival rate of rats subjected to intestinal ischemia reperfusion injury [6]. Other reports demonstrated that inhibition of inflammatory factors such as TNF-α, IL-6, and ICAM-1, as well as inhibition of lipid peroxidation can all protect kidneys against renal ischemia reperfusion-induced injury [7][8][9].…”
Section: Introductionmentioning
confidence: 99%